Characterising running economy and change of direction economy between soccer players of different playing positions, levels and sex. Issue 8 (3rd August 2022) - Dolci, Filippo; Kilding, Andrew; Spiteri, Tania; Chivers, Paola; Piggott, Ben; Maiorana, Andrew; Hart, Nicolas H.
ABSTRACT: Traditional movement economy (ME) measures the energetic cost of in-line running. However, it is debatable whether such a measure is representative of movement efficiency for team sport athletes who are required to run and change direction repeatedly. This study evaluated ME during both in-line running and runs with directional changes and provided a preliminary exploration as to whether these abilities discriminate soccer players according to playing position, level, and sex. Forty-three soccer players were assessed for ME as extrapolated from oxygen uptake during in-line running (RE) and running with changes of directions (using 20 and 10 m shuttle runs [SRE20 and SRE10 ]) at 8.4 km/h mean speed. ME worsened with change of direction frequency ( p  < 0.001). Coefficient of determination was high between RE and SRE20 ( r 2  =   0.601) but dropped below 0.5 for RE and SRE10 ( r 2  = 0.280) as change of direction frequency increased. No significant differences were observed between different player positions, however, centre midfielders reported the best ME across any position and running mode, with the largest differences observed in centre backs over SRE10 (41.9 ± 2.7 ml/kg/min [centre midfielders] vs 45 ± 1.8 ml/kg/min [centre backs]; ES = 1.19). No significant differences were observed for ME over any running condition for male players of different playing levels. Female players exhibited better ME than male players with significant differences observed for SRE10 (41.5 ± 2.6 ml/kg/min [females] vs 44 ± 2.6 ml/kg/min [males]; p  = 0.013; ES = 0.94). RE does not adequately account for efficiency during activities that involve changes of direction. SRE10 is a stronger discriminator of ME between soccer players of different position and sex.